Effect of corporate governance on bond yield and bond ratings : a study in Malaysia listed companies - Nieh, Vun Ru (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the relationship between the corporate governance, bond yields and bond ratings in Malaysia’s listed companies for nine time period starting year 2001 until 2009. Data are collected from annual report for each of the firms. Correlation, descriptive statistics, Ordinary Least Square, and Ordered Probit Model are the technique used to determine the relationship and significant linear relationship between the variables. The variables used includes dividend yield, institutional ownership, top five institutional ownership, outside directorship, debtto-equity ratio, maturity, margin, above five percent institutional ownership, ratings, bond issues size and total asset. There are 142 firms together for this study and 162 firms which include the firms that issues bond for several years are reported in the appendix. Bond ratings are gathering from Rating Agency Malaysia (RAM) and Malaysia Rating Corporation (MARC). Empirical results shows that ratings are significant with bond yields and are inversely correlated which followed Bhojraj and Sengupta (2003).